Imaging dose in breast radiotherapy: does breast size affect the dose to the organs at risk and the risk of secondary cancer to the contralateral breast?. Issue 1 (7th January 2015) - Batumalai, Vikneswary; Quinn, Alexandra; Jameson, Michael; Delaney, Geoff; Holloway, Lois
Abstract Introduction Correct target positioning is crucial for accurate dose delivery in breast radiotherapy resulting in utilisation of daily imaging. However, the radiation dose from daily imaging is associated with increased probability of secondary induced cancer. The aim of this study was to quantify doses associated with three imaging modalities and investigate the correlation of dose and varying breast size in breast radiotherapy. Methods Planning computed tomography (CT) data sets of 30 breast cancer patients were utilised to simulate the dose received by various organs from a megavoltage computed tomography (MV‐CT), megavoltage electronic portal image (MV‐EPI) and megavoltage cone‐beam computed tomography (MV‐CBCT). The mean dose to organs adjacent to the target volume (contralateral breast, lungs, spinal cord and heart) were analysed. Pearson correlation analysis was performed to determine the relationship between imaging dose and primary breast volume and the lifetime attributable risk (LAR) of induced secondary cancer was calculated for the contralateral breast. Results The highest contralateral breast mean dose was from the MV‐CBCT (1.79 Gy), followed by MV‐EPI (0.22 Gy) and MV‐CT (0.11 Gy). A similar trend was found for all organs at risk (OAR) analysed. The primary breast volume inversely correlated with the contralateral breast dose for all three imaging modalities. As the primary breast volume increases, the likelihood of a patient developing a radiation‐induced secondary cancer to the contralateral breast decreases. MV‐CBCT showed a stronger relationship between breast size and LAR of developing a radiation‐induced contralateral breast cancer in comparison with the MV‐CT and MV‐EPI. Conclusions For breast patients, imaging dose to OAR depends on imaging modality and treated breast size. When considering the use of imaging during breast radiotherapy, the patient's breast size and contralateral breast dose should be taken into account.